A Collaborative Digitalization Model for Strengthening Sustainable Tourism Ecosystems: An Agency Approach to Tourism Enterprises in Central Java - Widianti, Hesti; Yuwono, Setya Teguh; Ristanto, Himawan Ardhi; Aisyah, Alfiyani; Sya’bani, Mohammad (Ilomata International Journal of Management, 2026)
Introduction. The global tourism sector, contributing 10.3% to world GDP (UNWTO, 2024), is undergoing structural shifts driven by digital transformation, sustainability demands, and evolving tourist expectations. Although the pentahelix model is positioned as an ideal multi-stakeholder framework, its top-down implementation often remains rhetorical and fails to translate into concrete actions—particularly in Indonesian destinations where collaboration tends to be ceremonial. Methods. This participatory action research applied a mixed-methods sequential explanatory design involving 85 tourism business operators in Central Java (January-November 2025). A five-phase intervention was implemented: awareness building, digital capacity development (presence, engagement, distribution, conversion), collaborative design workshops, technical implementation support, and continuous monitoring. Data were collected through pre–post competency tests, participatory observations, three FGDs, digital artifact analysis, and digital metrics tracking. Analyses used paired t-tests, thematic analysis, and methodological triangulation Results. Bottom-up, industry-initiated collaboration substantially improved sustainability competence by 41.9% (M=58.3→82.7; p<0.001; d=2.21). Digital engagement metrics increased markedly: likes +156%, comments +203%, shares +187%, reach +142%, and Google Business Profile views +134%. Five tangible outputs emerged: an integrated event calendar coordinating 24 events; eight cross-destination bundled packages generating IDR 387 million and increasing length of stay from 1.2 to 2.3 days; a shared digital platform attracting 3,847 unique visitors and 78 direct bookings; standardized service protocols; and peer-learning networks. Conclusion. Community-driven digital collaboration effectively shifts competitive mindsets toward cooperative partnerships, with digital tools functioning as coordination infrastructure. The “Industry as Trigger–Pentahelix as Enabler” framework demonstrates that pentahelix activation occurs organically when grounded in evidence. Future research should conduct longitudinal assessments and cross-destination comparisons.